East Asia and the Pacific Region Urban Sanitation Review : Philippines Country Study - World Bank (Washington, DC, 2014)
This Philippines country study forms part of the East Asia and the Pacific region urban sanitation review that focuses on three of the emerging middle income countries of East Asia: Indonesia, Philippines, and Vietnam. The regional review aims to develop a strategic framework to help guide national urban sanitation programs and their implementation in these emerging middle income countries. This country study contributed to the regional review by providing important information on sector operations in the Philippines. The development of urban sanitation in the Philippines needs to be considered in the context of the different situations in Metro Manila and the other parts of the country. The case studies for some urban areas were prepared to see how sanitation operations are carried out in the Philippines and a consultative workshop was held on February 19, 2013 in Manila. The findings of the Philippines country study are briefly presented which complements the findings of the regional report.